Unlocking Smallholder Credit Does Credit-Linked Agricultural Insurance Work? - Meyer, Richard (World Bank E-Library Archive, 2017)
This paper reviews possibilities for, and experience with, credit-linked crop insurance, including different types of insurance and credit arrangements, ranging from insurance sold to individual farmers to meso insurance sold to financial service providers (FSPs) to cover losses suffered by farmer borrowers. The paper describes the main methods of linkage that are being tested or proposed, identifies the critical features of each method, and discusses the advantages and limitations for the three parties - farmers, FSPs, and insurers